SIFAT KIMIA TANAH PADA HUTAN PRIMER, LAHAN AGROFORESTRI DAN PERKEBUNAN KAKAO DI SUB DAS WERA SALUOPA DESA LEBONI KECAMATAN PAMONA PUSELEMBO KABUPATEN POSO - Ola Barek, Joko Suyono; Yusran, Yusran; Irmasari, Irmasari (Universitas Tadulako, 2015)
Land use and forest harvesting (timber and non-timber) is conducting logging activities that could lead to the opening of ground cover. This activity will lead to disruption of physical properties, chemical and biological soil, especially in the surface layer of soil.The purpose of this study was to determine the physical properties of soil on different types of land use, ie in primary forests, agroforestry and cocoa plantations in Sub Das Wera Saluopa which is part of the watershed area and Maraoa Koronjongi which took place in mey until July 2013. The study was conducted, the various types of land use in several stages starting from the orientation of the field, the determination of sample plots (primary forest, cocoa plantations and agroforestry land) soil sampling, laboratory analysis of soil samples and analysis of data, both field data as well as data from laboratory. Methods of implementation research is done in several stages starting from the orientation field, the determination of sample plots in different land use types (primary forest, cocoa plantations and agroforestry land) soil sampling, laboratory analysis of soil samples and analysis of data, both the data and the data from the field from the laboratory. For site selection was purposive sampling is the Saluopa Wera Sub-watershed, in the village of Leboni, District Puselemba Pamona, Poso district of Central Sulawesi.The results showed that the physical properties of the soil at various types of land use in the watershed Wera Sub Saluopa have sandy loam soil texture, soil permeability varies from very slow (primary forest) to very fast (agroforestry) soil porosity 49.93% (primary forest) , 54.04% (cocoa plantation) with high bulk density â‰¥ 1.0 with organic ingredients is the most high-growth forests (7.09) followed by cocoa plantation (5.86) and agroforestry land (4,12). Keyword: Primary Forest, Cocoa Plantations, Agroforestry.